Elongation of the retina and ciliary body in dependence of the sagittal eye diameter: retina - Panda-Jonas, Songhomitra; Auffarth, Gerd U.; Jonas, Jost B.; Jonas, Rahul A. (Investigative ophthalmology & visual science, 2022)
To examine the elongation of the retina and ciliary body in relation to myopic axial elongation. Using light microscopy, we histomorphometrically measured in enucleated human globes the length of the retina from the ora serrata to the optic disc borders. The total retinal length was the mean of the retinal length measurements obtained on both sides of the optic disc. We additionally determined the length of the ciliary body between the ora serrata and the scleral spur. The study included 174 eyes (mean age, 61.7 ± 14.8 years; range, 24-89 years) with a mean sagittal eye diameter of 25.9 ± 3.2 mm (range, 21.0-37.0 mm). Retinal length (beta, 0.81; nonstandardized regression coefficient B, 0.73; 95% confidence interval (CI), 0.65-0.81; P < 0.001) and ciliary body length elongated (beta, 0.49; nonstandardized regression coefficient B, 0.16; 95% CI, 0.12-0.20; P < 0.001) with a longer sagittal eye diameter. Retinal length and ciliary body length were associated with each other (beta, 0.34; nonstandardized regression coefficient B, 0.12; 95% CI, 0.07-0.17). The retina elongates by 0.73 mm (95% CI, 0.65-0.81) and the ciliary body by 0.16 mm (95% CI, 0.12-0.20) for each millimeter of axial elongation. With the inner limiting membrane and retinal nerve fibers forming the only structures connecting the deeper retinal layers with the optic disc, retinal elongation may be associated with a stretching of the retinal nerve fibers, potentially leading to optic nerve damage in highly myopic eyes, and with an increased strain within the inner limiting membrane, potentially leading to an intraretinal elevation at the posterior pole with the sequel of a myopic maculoschisis.
Gesehen am 02.10.2023